Ports: Definition and study of types, sizes and business models - Ivan Roa; Yessica Pe\~na; Beatriz Amante; María Goretti (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: In the world today there are thousands of port facilities of different types and sizes, competing to capture some market share of freight by sea, mainly. This article aims to determine the type of port and the most common size, in order to find out which business model is applied in that segment and what is the legal status of the companies of such infrastructure. Design/methodology/approach: To achieve this goal, we develop a research on a representative sample of 800 ports worldwide, which manage 90% of the containerized port loading. Then you can find out the legal status of the companies that manage them. Findings: The results indicate a port type and a dominant size, which are mostly managed by companies subject to a concession model. Research limitations/implications: In this research, we study only those ports that handle freight (basically containerized), ignoring other activities such as fishing, military, tourism or recreational. Originality/value: This is an investigation to show that the vast majority of the studied segment port facilities are governed by a similar corporate model and subject to pressure from the markets, which increasingly demand efficiency and service. Consequently, we tend to concession terminals to private operators in a process that might be called privatization, but in the strictest sense of the term, is not entirely realistic because the ownership of the land never ceases to be public
Keywords: 650; ports; concessions; load; management models; types of ports